2017
DOI: 10.1111/jav.01136
|View full text |Cite
|
Sign up to set email alerts
|

A small badge of longevity: opposing survival selection on the size of white and black wing markings

Abstract: According to handicap principle, exaggerated ornamental traits are supposed to exert costs on their bearers. However, there is much less theoretical and practical consensus about whether and under which conditions ornament expression should positively correlate with survival. We measured age‐related variation and survival selection on the size of white wing patches and black wing tips in a long‐lived monogamous seabird, the common gull Larus canus. Males had larger white patches than females but patch size sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 97 publications
4
8
0
Order By: Relevance
“…Middle-aged birds started egg-laying and had larger wing patches than young and old individuals. This result is consistent with the previous findings of the longitudinal studies from the same population, demonstrating senescence in annual fitness (Rattiste 2004;Brommer and Rattiste 2008) and wing patch size (Sepp et al 2017). Previous study in the same population (Sepp et al 2017) suggested that size of the white wing patch in common gulls may serve as an honest handicap signal of individual quality: possessing unpigmented areas in the tip of the wing is probably costly as feather breakage is more likely in the sites that lack protection by melanin (reviewed by Burtt 1986).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Middle-aged birds started egg-laying and had larger wing patches than young and old individuals. This result is consistent with the previous findings of the longitudinal studies from the same population, demonstrating senescence in annual fitness (Rattiste 2004;Brommer and Rattiste 2008) and wing patch size (Sepp et al 2017). Previous study in the same population (Sepp et al 2017) suggested that size of the white wing patch in common gulls may serve as an honest handicap signal of individual quality: possessing unpigmented areas in the tip of the wing is probably costly as feather breakage is more likely in the sites that lack protection by melanin (reviewed by Burtt 1986).…”
Section: Discussionsupporting
confidence: 93%
“…This result is consistent with the previous findings of the longitudinal studies from the same population, demonstrating senescence in annual fitness (Rattiste 2004;Brommer and Rattiste 2008) and wing patch size (Sepp et al 2017). Previous study in the same population (Sepp et al 2017) suggested that size of the white wing patch in common gulls may serve as an honest handicap signal of individual quality: possessing unpigmented areas in the tip of the wing is probably costly as feather breakage is more likely in the sites that lack protection by melanin (reviewed by Burtt 1986). Thus only individuals in superior condition (that being, for example, stronger feather structure, more protective preen gland, or ability to avoid situations where feathers may break) can afford large unpigmented areas in wingtips, and the size of these areas enables them to signal their prime condition (Zahavi 1975).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations